Affordable Housing and Vulnerable Households: An Analysis to Prevent Elderly Social Exclusion - Santos, António Duarte (2019)
Affordable housing has been developed to meet one of the main indicators to assess housing quality and boost social cohesion. This implies availability of housing space. The impact of demographic ageing is the most significant element for a European housing model, which is visible in southern European countries. The number of elderly who are still active is decreasing while the number of elderly who are retired is increasing. The percentage of elderly population will grow significantly throughout the next decades, as the baby-boom generation retires. This will lead to the increase in price to rent ratio vs price to income ratio to support active citizens and will cause families to pay more for housing, utilities (water, electricity and gas) and maintenance. In Southern Europe, this age group owns the worst and most run-down housing facilities. The refurbishing of city centres varies in the different countries and is slowing down. The private housing sector is being pressured due to the elderly’s low income. In the best-case scenario, cohabitation and the number of homeless will not decrease. This study analyses the recent changes in housing and social indicators in southern European countries in the scope of three aspects: the context of the dual housing market, housing conditions and public policies aimed at housing for the most vulnerable and for the elderly. Our results allow us to discuss data comparability, indicator trend variation in each country and debatable outcomes.